2009
DOI: 10.4269/ajtmh.2009.09-0294
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genetic Heterogeneity of Bartonella Strains Cultured from Rodents from 17 Provinces in Thailand

Abstract: Abstract. To study the distribution and diversity of Bartonella in rodents from Thailand, 330 rodents belonging to 13 species were tested. The majority (80.6%) of rodents examined belonged to the genus Rattus . Bartonellae were cultured from 41.5% of the rodents with a wide range of prevalence by host species and regions. Sequencing of gltA revealed diverse Bartonella strains. Bartonellae from Rattus spp. belonged to 23 variants and clustered with Bartonella coopersplainensis , Bartonella elizabethae , Bartone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
69
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(74 citation statements)
references
References 21 publications
5
69
0
Order By: Relevance
“…Although only five isolates of Bartonella were obtained, the finding of two different species, B. queenslandensis and B. tribocorum, among our small sample of rats from Salvador was unexpected. Infection with B. queenslandensis has been demonstrated from rats in Australia (Gundi et al 2009), while B. tribocorum is associated with rats from Thailand (Bai et al 2009). Although both species were found in the same rat population sampled from Los Angeles, California (Gundi et al 2012), only one rat was infected with B. queenslandensis compared to 54 rats infected with B. tribocorum.…”
Section: Discussionmentioning
confidence: 99%
“…Although only five isolates of Bartonella were obtained, the finding of two different species, B. queenslandensis and B. tribocorum, among our small sample of rats from Salvador was unexpected. Infection with B. queenslandensis has been demonstrated from rats in Australia (Gundi et al 2009), while B. tribocorum is associated with rats from Thailand (Bai et al 2009). Although both species were found in the same rat population sampled from Los Angeles, California (Gundi et al 2012), only one rat was infected with B. queenslandensis compared to 54 rats infected with B. tribocorum.…”
Section: Discussionmentioning
confidence: 99%
“…References according to continents and countries: Africa, Algeria, Bitam et al 2009;Egypt, Inoue et al 2009;Ethiopia, Meheretu et al 2013;DR Congo and Tanzania, Gundi et al 2012b;Nigeria, Kamani et al 2013;South Africa, Pretorius et al 2004, Brettschneider et al 2012b, Trataris et al 2012Tunisia, Fichet-Calvet et al 2000;Asia, Bangladesh, Bai et al 2007b;Cambodia, Lao PRD, and Thailand, Jiyipong et al 2012;China, Ying et al 2002, Ye et al 2009, Inoue et al 2009, Liu et al 2010Indonesia, Winoto et al 2005;Israel, Harrus et al 2009, Morick et al 2009Japan, Inoue et al 2008, Kabeya et al 2011Lao PDR, Angelakis et al 2009;Nepal, Gundi et al 2010;Taiwan, Lin et al 2008, Hsieh et al 2010, Tsai et al 2010, Chae et al 2008; Russia (Far east), Mediannikov et al 2005; South Korea, Kim et al 2005;Thailand, Castle et al 2004, Bai et al 2009, Saisongkorh et al 2009, Inoue et al 2009; Turkey (Kaman, Kirsehir), Karagöz et al 2013;America, Brazil, Costa et al 2014;Canada, Jardine et al 2005, Jardine et al 2006bPeru, Birtles et al 1999; United States, Kosoy et al 1997, Ellis et al 1999, Bown et al 2002, 2004a…”
Section: Figmentioning
confidence: 99%
“…are clustered in a common lineage, with the exception of B. rochalimae and B. tamiae (Buffet et al 2013a), evidencing the occurrence of an adaptive evolution of these bacteria in rodents (Engel et al 2011). Moreover, several molecular studies have found a wider variety of Bartonella genotypes that have challenged the current taxonomic classification (Bai et al 2009, Harrus et al 2009, Inoue et al 2009). To clarify the vast rodent-bartonellae diversity, the use of alternative taxonomic classification according to species complexes has been proposed .…”
Section: Figmentioning
confidence: 99%
“…Among these, rats of the genus Rattus were the most widely distributed and prevalent, being found in all study areas. For example, in the survey of bartonella infections in rodents from 17 provinces of Thailand, the total number of Rattus rats accounted for more than 80% of the tested rodents (Bai et al, 2009b); in studies in southwestern China and Bangladesh, more than 50% rodents also were Rattus rats (Ying et al, 2002;Bai et al, 2007b). Nevertheless, the most common Rattus species varied among the study sites.…”
Section: Rodent Communitymentioning
confidence: 99%
“…This study revealed the important finding that Rattus rats are the reservoir hosts of B. elizabethae, a bartonella strain associating with human diseases. With this discovery, more investigations of bartonella infections in rodents were later carried out in several other tropical countries, including Bangladesh, Thailand, Vietnam, Indonesia, Kenya, and others (Castle et al, 2004;Winoto et al, 2005;Bai et al, 2007bBai et al, & 2009bKosoy et al, 2009 & unpublished data). In this section, we compare the composition of rodent community, bartonella prevalence, and genetic diversity of the Bartonella strains, mainly based on three most complete studies that were conducted in southwestern China, Bangladesh, and Thailand (Ying et al, 2002;Bai et al, 2007bBai et al, & 2009b.…”
Section: Bartonella Infections In Rodents In Tropicsmentioning
confidence: 99%